Application of Canny Method to Detect Vehicle License Plate in Tanjung Balai City Government Mess Area - Aini, Siti Nurul; Kurniawan, Rakhmat (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Vehicles have a license plate that serves to be the identity of a vehicle. The shape of the plate is in the form of a piece of metal mounted on the vehicle as an official identity. Making a license plate or Motor Vehicle Number Sign in Indonesia is regulated in Government Regulation No. 60 of 2016 with a validity period of 5 years. The regulation is about the type and tariff of Non-Tax State Revenue (BNBP), and has been officially enacted on January 6, 2017, by replacing Government Regulation No.50 of 2010, quoted from the Kompas newspaper website. Image is one of the components of multimedia that plays an important role because it contains information in visual form. Images have more information that can be conveyed than in the form of text. An image is a collection of image elements (pixels) that as a whole record a scene through a visual sensory (camera). Canny edge detection can detect edges with a minimum error rate, canny edge detection has a difference with other operators because it uses a Gaussian Derivative Kernel that can refine the appearance of the image. Good location can minimize the distance of edge detection produced by processing, so that the location of the edge can be detected similar to the real edge. The accuracy value of applying this method reaches 99.88%-100%. And lastly, one response to single edge that can produce a single edge, not giving false edges.